Anisotropic electroactive elastomer for highly maneuverable soft robotics. Issue 14 (26th March 2020) - Xiao, Youhua; Mao, Jie; Shan, Yejie; Yang, Tao; Chen, Zheqi; Zhou, Fanghao; He, Jin; Shen, Youqing; Zhao, Junjie; Li, Tiefeng; Luo, Yingwu
Abstract : Ultrathin anisotropic dielectric elastomer films of triblock copolymers were fabricated, enabling highly maneuverable soft crawlers actuated by sub-kV voltage. Abstract : Dielectric elastomers (DEs) are promising electroactive artificial muscles for use in soft machines. However, achieving anisotropy and sub-kV actuation voltage remains a great challenge for DE actuators. Herein, we report a facile method to fabricate ultrathin anisotropic DE films of an amorphous triblock copolymer poly(styrene- b -butyl acrylate- b -styrene) (SBAS) for soft actuators. The modulus of anisotropic SBAS in one direction can be modulated from 0.3 MPa to 10.5 MPa, and the modulus in the orthogonal direction remains the same as that of the pristine film (0.3 MPa). The anisotropy endows soft DE actuators with the directional-preferred response to an applied electric field and programmable multiple actuation morphs. These anisotropic SBAS films allowed us to fabricate compact soft robotics with high maneuverability, including soft grippers for object manipulation and crawling robots with reversible moving ability under an actuation voltage around 800 V.